2011
DOI: 10.5194/amt-4-2213-2011
|View full text |Cite
|
Sign up to set email alerts
|

Improved identification of clouds and ice/snow covered surfaces in SCIAMACHY observations

Abstract: Abstract. In the ultra-violet, visible and near infra-red wavelength range the presence of clouds can strongly affect the satellite-based passive remote sensing observation of constituents in the troposphere, because clouds effectively shield the lower part of the atmosphere. Therefore, cloud detection algorithms are of crucial importance in satellite remote sensing. However, the detection of clouds over snow/ice surfaces is particularly difficult in the visible wavelengths as both clouds an snow/ice are both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In fact, retrievals of cloud microphysical and optical properties using only visible wavelengths are strongly biased by a bright surface (Platnick et al, 2001(Platnick et al, , 2004Platnick and King, 2003;Krijger et al, 2011). To overcome this limitation, near-infrared channels are introduced in the retrieval algorithms instead of the visible channel used over dark surfaces.…”
Section: Schäfer Et Al: 3-d Influence Of Ice Edges On Radiative Tmentioning
confidence: 99%
“…In fact, retrievals of cloud microphysical and optical properties using only visible wavelengths are strongly biased by a bright surface (Platnick et al, 2001(Platnick et al, , 2004Platnick and King, 2003;Krijger et al, 2011). To overcome this limitation, near-infrared channels are introduced in the retrieval algorithms instead of the visible channel used over dark surfaces.…”
Section: Schäfer Et Al: 3-d Influence Of Ice Edges On Radiative Tmentioning
confidence: 99%
“…This is how airborne observations can assist space-borne retrievals, as the aircraft can go back and observe what is inside and underneath the cloud that was remotely sensed. Additionally, satellite observations are often obstructed by the low contrast between clouds and the snow-or ice-covered surface (Krijger et al, 2011). In general, airborne or ground-based cloud observations are scarce, especially over the Arctic Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Tsay and Jayaweera (1984) showed that Arctic stratus has a considerable horizontal homogeneity of cloud morphology, droplet diameter, concentration, and liquid water content, except for the cloud top layer. Here, mixing results in small-scale inhomogeneities identified by Lawson et al (2001) and Klingebiel et al (2015): bi-modal cloud particle size distributions at cloud top, while mono-modal distributions dominate the lower cloud layers representative for the adiabatic and homogeneous character of the clouds. In contrast, sea ice has irregular top and bottom surfaces and is broken into distinct pieces, called floes (Rothrock and Thorndike, 1984).…”
Section: Introductionmentioning
confidence: 93%